Wikipedia – amatørenes inntog - Nyborg, Chris (LexicoNordica, 2007)
Wikipedia is the entry of amateurs into the world of encyclopaedias. Volunteers with no background in lexicography are building a massive project from scratch. The article, based on a presentation given in January 2007, outlines the mechanisms and processes involved in Wikipedia’s explosive growth. By trial and error, the contributors work out the project’s rules as they go along. Many Wikipedians become interested in exploring the theory and practice of creating an encyclopaedia, combining traditional lexicographical concepts with Wikipedia’s focus on freedom of information and the ability of anyone to contribute.